2009
DOI: 10.1093/carcin/bgp166
|View full text |Cite
|
Sign up to set email alerts
|

(-)-Epigallocatechin gallate downregulates EGF receptor via phosphorylation at Ser1046/1047 by p38 MAPK in colon cancer cells

Abstract: We previously reported that (-)-epigallocatechin gallate (EGCG) in green tea alters plasma membrane organization and causes internalization of epidermal growth factor receptor (EGFR), resulting in the suppression of colon cancer cell growth. In the present study, we investigated the detailed mechanism underlying EGCG-induced downregulation of EGFR in SW480 colon cancer cells. Prolonged exposure to EGCG caused EGFR degradation. However, EGCG required neither an ubiquitin ligase (c-Cbl) binding to EGFR nor a pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
69
1

Year Published

2010
2010
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(73 citation statements)
references
References 34 publications
3
69
1
Order By: Relevance
“…We have previously reported that (Ϫ)-epigallocatechin gallate, as well as HSP90 inhibitors, causes down-regulation of the EGFR via phosphorylation at Ser-1046/7 through p38 MAPK in human cancer cells (24,26). Additionally, accumulating evidence shows that activation of p38 MAPK has an inhibitory effect on tumorigenesis (55,56) and that a variety of agents, such as gemcitabine (5) and cisplatin (20), can also induce activation of p38 MAPK and internalization of EGFR into endosomal vesicles.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously reported that (Ϫ)-epigallocatechin gallate, as well as HSP90 inhibitors, causes down-regulation of the EGFR via phosphorylation at Ser-1046/7 through p38 MAPK in human cancer cells (24,26). Additionally, accumulating evidence shows that activation of p38 MAPK has an inhibitory effect on tumorigenesis (55,56) and that a variety of agents, such as gemcitabine (5) and cisplatin (20), can also induce activation of p38 MAPK and internalization of EGFR into endosomal vesicles.…”
Section: Discussionmentioning
confidence: 99%
“…We have recently reported that phosphorylation of EGFR at serine 1046/7 via activation of p38 MAPK plays a pivotal role in down-regulation of EGFR induced by (Ϫ)-epigallocatechin gallate (24), anisomycin (25), and HSP90 inhibitor (26). Moreover, there is an evidence that cisplatin also induces EGFR internalization, which is mediated by p38 MAPK-dependent phosphorylation of the receptor at threonine 669 (20).…”
Section: Members Of the Egf Receptor (Egfr)mentioning
confidence: 99%
“…We have previously reported that (-)-epigallocatechin gallate (EGCG) caused internalization of EGFR into endosomal vesicles (23). Moreover, we have recently shown that EGCG downregulates EGFR via phosphorylation at Ser1046/7 by p38 MAPK in colon cancer cells (25). In the present study, we investigated the involvement of p38 MAPK in EGFR desensitization induced by HSP90 inhibitors and showed that p38 MAPK activated by HSP90 inhibitors induced desensitization of EGFR via its phosphorylation at Ser1046/7.…”
Section: Discussionmentioning
confidence: 75%
“…1B-D, upper panels). In addition, we examined the effects of 17-AAG on the phosphorylation of EGFR at Ser1046/7, since this phosphorylation has been reported to play an important role in EGFR desensitization (20,25). Interestingly, 17-AAG induced phosphorylation of EGFR at Ser1046/7 at a peak of 30 min to 1 h (Fig.…”
Section: -Aag Caused Desensitization Of Egfr Concurrently Inducingmentioning
confidence: 96%
“…Immunofluorescence microscopy was performed as described previously (15). The cells grown on coverslip-bottom dishes were first exposed to UV-C (200 J) and incubated for 6 h at 37˚C, followed by exposure to Hoechst 33258 for 30 min in RPMI containing 1% bovine serum albumin (BSA).…”
Section: Methodsmentioning
confidence: 99%